2021
DOI: 10.1007/s10532-021-09948-9
|View full text |Cite
|
Sign up to set email alerts
|

Sediments in the mangrove areas contribute to the removal of endocrine disrupting chemicals in coastal sediments of Macau SAR, China, and harbour microbial communities capable of degrading E2, EE2, BPA and BPS

Abstract: The occurrence of endocrine disrupting chemicals (EDCs) is a major issue for marine and coastal environments in the proximity of urban areas. The occurrence of EDCs in the Pearl River Delta region is well documented but specific data related to Macao is unavailable. The levels of bisphenol-A (BPA), estrone (E1), 17α-estradiol (αE2), 17β-estradiol (E2), estriol (E3), and 17α-ethynylestradiol (EE2) were measured in sediment samples collected along the coastline of Macao.BPA was found in all 45 collected samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 84 publications
1
4
0
Order By: Relevance
“…In wastewater treatment plants of 282 municipal wastewater treatment plants across 29 countries, 17α-ethinylestradiol in influent and effluent is up to 7890 and 549 ng L −1 [ 51 ]. Still in wastewater treatment plants also, similarly, a previous study in Macao, China, presented that 17α-ethinylestradiol has been detected up to 0.96 ng g −1 in the wastewater treatment plant, 0.35 ng g −1 dw in the ecological zone, 0.48 ng g −1 dw in Taipa, and 0.38 ng g −1 dw in an industrial area [ 52 ]. Other estrogen particulate concentrations, such as estrone, 17β-estradiol, and estriol, were inspected up to 14.4 ng g −1 , 16.6 ng g −1 , and 37.5 ng g −1 in the SPM of Yangzi River in China [ 53 ].…”
Section: Biotoxicity Of Pharmaceutical Active Compoundssupporting
confidence: 60%
“…In wastewater treatment plants of 282 municipal wastewater treatment plants across 29 countries, 17α-ethinylestradiol in influent and effluent is up to 7890 and 549 ng L −1 [ 51 ]. Still in wastewater treatment plants also, similarly, a previous study in Macao, China, presented that 17α-ethinylestradiol has been detected up to 0.96 ng g −1 in the wastewater treatment plant, 0.35 ng g −1 dw in the ecological zone, 0.48 ng g −1 dw in Taipa, and 0.38 ng g −1 dw in an industrial area [ 52 ]. Other estrogen particulate concentrations, such as estrone, 17β-estradiol, and estriol, were inspected up to 14.4 ng g −1 , 16.6 ng g −1 , and 37.5 ng g −1 in the SPM of Yangzi River in China [ 53 ].…”
Section: Biotoxicity Of Pharmaceutical Active Compoundssupporting
confidence: 60%
“…The E2 degrading strain ED55 was previously isolated from sediments of a discharge point of a WWTP in Coloane (Macau) for their capacity to degrade EDCs, when supplied as a sole source of carbon [ 24 ]. Strain ED55 morphology was examined by light microscopy, which revealed rod-shaped cells.…”
Section: Resultsmentioning
confidence: 99%
“…The E2 degrading strain named ED55 was previously isolated after the enrichment of sediments of a discharge point of a WWTP in Coloane, Macau [ 24 ]. In order to obtain the complete sequence of the 16S rRNA gene, genomic DNA extraction and further amplification by polymerase chain reaction (PCR) were performed as described elsewhere [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…6 During the life cycle of products, BPA is inevitably released into the environment, while an increasing number of studies have found that BPA is detected in various environmental media and even in human bodies. [7][8][9][10] Exposure to BPA can cause adverse health effects in animals and humans, including diabetes, reproductive diseases, and cardiovascular diseases. 4,[11][12][13][14] Therefore, laws and regulations have been enacted in the European Union, the United States, and China to restrict or prohibit the use of BPA.…”
Section: Introductionmentioning
confidence: 99%